Violent and risk-taking behaviors associated with intake of energy drinks mixed with alcohol and perceptions of this consumption among children and adolescents in Costa Rica - Núñez Rivas, Hilda Patricia (2020)
Introduction: The consumption of energy drinks and its mix with alcohol has been associated with negative and violent behaviors in youngsters. Objective: Determine the risk-taking behaviors associated with the consumption of energy drinks mixed with alcohol in Costa Rican adolescents. Methods: A mixed cross-sectional study was performed with a population of 2667 students of 64 educative centers in 2016. Descriptive statistics were performed with the program SPSS 20.0 and a value of p ˂0.05 was considered significant. Results: The third part of the study population is usually a consumer of energy drinks (30%) and 3% make use of drinks mixed with alcohol. The children and adolescents, who consume energy-alcohol mixed drinks, are more likely to present risk-taking behaviors than those who do not consume these mixed beverages: combined use of medicines to get high; cocaine consumption, consumption of cement / glue, consumption of marijuana, physical violence (fighting), use of weapons, suicidal ideation, deliberate self-harm, low educational expectation, sexual intercourses, cyberbullying and school apathy. The students perceived the intake of energy beverages as of low risk for their health. They also agree that frequent consumption is because drinks have good flavors and nice logo designs and the ability to stay awake and with more energy for longer periods of time in order to improve in academic homework, sports performance and to endure more the consumption of alcoholic beverages. Conclusions: Public health policies should consider controlling the publicity aimed to children and adolescents regarding the marketing of energy and alcoholic drinks.